Couples Coping With Hematological Cancer: Support Within and Outside the Couple – Findings From a Qualitative Analysis of Dyadic Interviews - Bodschwinna, Daniela; Weissflog, Gregor; Döhner, Hartmut; Niederwieser, Dietger; Mehnert-Theuerkauf, Anja; Gündel, Harald; Ernst, Jochen; Goerling, Ute; Hönig, Klaus (Frontiers in Psychology, 2022)
Objective Cancer affects the patients as well as their partners. Couples use different strategies to cope with cancer and the associated burden: individual coping, dyadic coping, and support from the social network and from professional health care. The aim of this qualitative dyadic interviews is to gain a deeper and more differentiated understanding of the support system inside and outside of the couple. Methods Ten heterosexual couples (patients: seven men and three women) with different ages (patients: range = 22–75; spouses: range = 22–74), different hematological cancer (e.g., acute myeloid leukemia, non-Hodgkin’s lymphoma) and cancer stages (initial diagnosis or relapse) participated in the study. Semi-structured dyadic interviews were conducted. Data of the verbatim transcripts were systematically coded and analyzed following structuring content analysis. Results Three main categories (individual coping, dyadic coping, and outside support) and ten subcategories about coping and support strategies in hematological cancer patients and their spouses could be identified. All couples described cohesion in relationship as an essential common dyadic coping strategy. Most strategies were focused on the patient’s wellbeing. Furthermore, couples reported different common plans for the future: while some wanted to return to normality, others were reaching out for new goals. Conclusion Couples used various coping and support strategies, that differed in type and frequency between patients and spouses. Most of the strategies were perceived as beneficial, but some also triggered pressure. Overall, spouses seem to need more psychological support to improve their own wellbeing.